2019
DOI: 10.2478/achi-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli Responsive Hydrogels: NIPAM/AAm/Carboxylic Acid Polymers

Abstract: Stimuli-responsive hydrogels (SRH) were prepared by using monomers (i.e. N-isopropyl acrylamide; NIPAM and acrylamide; AAm), co-monomers (i.e. methacrylic acid; MPA or mesaconic acid; MFA) and a crosslinker (N, N’-methylene bisacrylamide; N-Bis). SRH have been prepared by thermal free radical polymerization reaction in aqueous solution. Spectroscopic and thermal analyses such as Fourier Transform Infrared Spectroscopy, thermogravimetric analysis and differential scanning calorimetry analysis were performed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(60 reference statements)
1
6
0
Order By: Relevance
“…In general, acrylamide-based compounds are well known for their absorptive and medicinal properties. In line with our research interest in AAm based materials, [17][18][19][20][21][22] in this article we report the copolymerization of NIPAAm with AAm. The present study aims to develop N-isopropyl acrylamide/acrylamide; (NI-PAAm/AAm) based hydrogels with pH and temperature sensitivities and higher swelling properties.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…In general, acrylamide-based compounds are well known for their absorptive and medicinal properties. In line with our research interest in AAm based materials, [17][18][19][20][21][22] in this article we report the copolymerization of NIPAAm with AAm. The present study aims to develop N-isopropyl acrylamide/acrylamide; (NI-PAAm/AAm) based hydrogels with pH and temperature sensitivities and higher swelling properties.…”
Section: Introductionsupporting
confidence: 68%
“…In the FTIR spectra of the SHs (Figure 2), the typical absorption bands for NIPAAm, AAm, and A or M units can be seen about 3600-3100 cm −1 as broad bands for secondary NH amide, between 2980 and 2878 cm −1 for CH stretching frequencies for isopropyl groups, and at 1670 cm −1 a strong C=O amide I band, and at 1550 cm −1 for another strong amide II band. The peak around 1400-1300 cm −1 belongs to −CH(CH3)2 group in isopropylgroups [18,20,24]. From this spectral analysis, it can be concluded that a polymeric network is formed, because of the functional groups of each component of the hydrogel units: NIPAAm, AAm, and A or M monomers with NBis.…”
Section: Ftir Analysismentioning
confidence: 81%
See 1 more Smart Citation
“…Temperature, light Mesogen-driven network deformation Oseen, 1933;Frank, 1958;Ericksen, 1961;Stephen and Straley, 1974;De Gennes and Prost, 1993;Terentjev, 1996, 2007;Finkelmann et al, 2001;Ikeda et al, 2007;Ohm et al, 2012;Jiang et al, 2013;White and Broer, 2015;Yakacki et al, 2015;Guin et al, 2018;McBride et al, 2018;Ula et al, 2018;Shang et al, 2019 Gels Hydrogels Humidity, other fluids Swelling-driven response Flory, 1950;Tanaka and Fillmore, 1979;Hong et al, 2008;Zhu et al, 2018;Agarwal et al, 2019 PNIPAm Humidity, other fluids, temperature change Temperaturedependent swelling-driven response Afroze et al, 2000;Yan and Tsujii, 2005;Deshmukh et al, 2013;Li et al, 2015;Vernerey and Shen, 2017;Işikver and Saraydin, 2019;Shen et al, 2019;Wang et al, 2020 PNIPAm, poly(N-isopropylacrylamide).…”
Section: Polymers With Conformational Instabilitiesmentioning
confidence: 99%
“…Among the family of gels, poly(N-isopropylacrylamide) (also indicated as PNIPAA or PNIPAm) forms a three-dimensional hydrogel when cross-linked with N, N ′ -methylene-bisacrylamide (MBAm) or N, N ′ -cystamine-bis-acrylamide (CBAm) (Işikver and Saraydin, 2019). It is a gel whose fluid absorption capability is heavily influenced by the temperature; in fact, it is a temperature-responsive polymer showing a reversible lower critical solution temperature (LCST) phase transition from a swollen state to a shrunken dehydrated one (Yan and Tsujii, 2005).…”
Section: Temperature-sensitive Hydrogelsmentioning
confidence: 99%